Alcohol fuels in SI engines: a comprehensive state-of-the-art review on combustion, performance, and environmental impacts - Srikrishnan, Guruprasad; Shenbagamuthuraman, V.; Agbulut, Umit; Mishra, Ishani; Jain, Jesika; Balusamy, Saravanan; Chinnadurai, Karthick; Chatterjee, Dipankar; Shankar, E.; Shaik, Saboor; Hoang, Anh Tuan; Saleel, C. Ahamed; et al. (SPRINGER, 2024)
The search for alternative fuels compatible with internal combustion engines has escalated as a result of worldwide pollution and the exhaustion of fossil resources. Alcoholic fuels, such as methanol, ethanol, butanol, and fusel alcohols, are being considered as viable alternatives to gasoline and gaseous fuels. This review analyzes the effects of alcoholic fuels on the performance, combustion, and emissions of spark-ignition (SI) engines. It specifically focuses on several fuel supply modes, including blending, dual mode, and dedicated (100%) modes. This paper examines the impact of fuel characteristics on engine parameters and investigates various operating settings to improve performance. Furthermore, it tackles the existing difficulties linked to the use of alcoholic fuel blends in spark-ignition (SI) engines and puts forward alternative remedies. Special emphasis is placed on ethanol, which has shown to possess adequate fuel mixture characteristics for spark-ignition (SI) engines in current circumstances. The analysis identifies deficiencies in current research, particularly concerning the combustion of fusel alcohol in direct injection (DI) and port-fuel injection (PFI) engines. It underscores the necessity for more investigations into the long-term durability of engines and the compatibility of materials with alcohol fuels. This article intends to provide a thorough overview that will direct future research and development endeavors toward achieving a more sustainable and efficient utilization of alcoholic fuels in internal combustion engines.
Keywords: Alternative fuel; Combustion; Performance; Emission; Spark-ignition engines; Alcohol; SPARK-IGNITION ENGINE; ETHANOL-GASOLINE BLENDS; ISO-BUTANOL ADDITIVES; N-BUTANOL; DUAL-FUEL; FUSEL OIL; EMISSION CHARACTERISTICS; COMPRESSION RATIO; UNLEADED GASOLINE; EXHAUST EMISSIONS; Thermodynamics; Chemistry